Educational Opportunities in BME Specialization - Tradition, Culture and Perspectives - Marta, Wasilewska-Radwanska; Ewa, Augustyniak; Ryszard, Tadeusiewicz; Piotr, Augustyniak (IntechOpen, 2012)
None